Online business platforms and international trade - Jerónimo Carballo; Marisol Rodriguez Chatruc; Catalina Salas Santa; Christian Volpe Martincus (Inter-American Development Bank (IDB), 2020)
International trade is subject to information incompleteness. Firms must therefore engage in a costly search process to find business partners. Online platforms can reduce these search costs and thereby favor firms exports. We examine whether this is actually the case and the underlying mechanisms thereof by focusing on ConnectAmericas, a free, purely informational online platform that, by the end of 2018, connected more than 45,000 firms from 140 countries. In particular, we estimate the impact of using the platform on firms foreign sales utilizing detailed data on both firms participation therein and the entire universe of export transactions for Peru over the period 2010-2018. In so doing, we apply a difference-in-differences strategy and specifically exploit visits firms received to their profiles as a source of identifying variation. Consistent with the interpretation of the platform as a search cost-reducing mechanism, our estimates suggest that ConnectAmericas resulted in increased firms exports, particularly from those that had no digital presence, of differentiated products, and to less familiar destinations.
Keywords: F10; F13; F14; D83; L15; L86; 330; Information Frictions; Online Platforms; Exports; Firms